Ultra-high annealing twin density in <211>-oriented Cu films. (15th July 2020) - Chen, Kuan-Ju; Chen, Jui-Yuan; Ting, Yi-Hsin; Wu, Wen-Wei; Chen, Chih
Abstract: We reported the fabrication of densely twinned Cu films with highly (211) texture developed from the annealing of <111>-oriented nanotwinned copper (nt-Cu) films. During the annealing at 300 °C, abnormal grain growth occurred in the nt-Cu film and resulted in a microstructure dominated by the anomalously large <211>-oriented grains. Moreover, densely-intersected annealing twin bands with <221>, <611>, and <931> orientations are embedded in the large <211> grains. The measured annealing twin density is 0.2 µm −1, which is highest among the reported values in previous literatures with similar grain size. Extensive multiple twinning process may occur during the annealing to form the unique microstructure. Graphical abstract: We reported the fabrication of densely twinned Cu films with highly (211) texture developed from the annealing of <111>-oriented nanotwinned copper (nt-Cu) films. During the annealing at 300 °C, abnormal grain growth occurred in the nt-Cu film and resulted in a microstructure dominated by large <211>-oriented grains embedded with densely-intersected annealing twin bands with <221>, <611>, and <931> orientations, as shown in Fig (a) below. The measured annealing twin density is 0.2 µm −1, which is highest among the reported values in previous literatures. The boundaries shown in red in Fig (b) represent the ∑3 twin boundaries. Image, graphical abstract